Role of Schmallenberg virus infection in congenital malformations in ruminants in Scotland in spring 2017. (30th September 2017) - Brülisauer, F.; Scholes, S.; Caldow, G. L.; Rocchi, M.; Dagleish, M. P.; Chianini, F.
Abstract : Scotland's Rural College (SRUC), together with the Moredun Research Institute, carries out surveillance for Schmallenberg virus (SBV) infection in cattle and sheep. This article reports findings relating to diagnoses of fetopathy associated with SBV infection and other congenital malformations in these species made between January 1 and May 5, 2017.